Epidemiological profile of maternal deaths in a referral hospital for high-risk pregnancy - Menezes, Maria Lucia Neto; Bezerra, Joana de Faria Oliveira; Bezerra, Julia de Faria Oliveira (Rev Rene, 2015)
Objective: to describe the epidemiological profile of maternal deaths in a referral public hospital. Methods: it is aretrospective, descriptive study of cross-section type. Variables in the death certifications and maternal death investigationforms were analyzed. Results: there were 93 cases recorded, corresponding to the ratio of 228.4 maternal deaths per100,000 live births. Most of these deaths were from women aged 20-29 years old (47.3%), undergoing cesarean section(39.8%). Most deaths occurred in the postpartum period (66.7%), by direct obstetric causes (55.9%), especially: infection(28%), cardiovascular disease (20.4%) and lung disease (10.8%). Conclusion: maternal deaths occurred in a context ofsocio-economic unfavorable condition, especially affecting young women, black, victimized by infectious conditions andcardiovascular diseases. The importance of improving the quality of records, surveillance deaths and postnatal care wereevident.